2016
DOI: 10.1158/1535-7163.mct-15-0987
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Inhibits Breast Cancer Growth by Blocking the Tumor-Promoting Feedforward Loop between Cancer Cells and Macrophages

Abstract: Macrophage infiltration correlates with severity in many types of cancer. Tumor cells recruit macrophages and educate them to adopt an M2-like phenotype through the secretion of chemokines and growth factors, such as MCP1 and CSF1. Macrophages in turn promote tumor growth through supporting angiogenesis, suppressing anti-tumor immunity, modulating extracellular matrix remodeling, and promoting tumor cell migration. Thus tumor cells and macrophages interact to create a feedforward loop supporting tumor growth a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 49 publications
2
67
0
Order By: Relevance
“…In mice bearing EO771 or 4T1 breast tumors, emodin suppressed tumor growth by inhibiting macrophage infiltration and M2-like polarization, accompanied by increased T-cell activation and reduced tumor angiogenesis (Iwanowycz et al, 2016). At molecular level, emodin inhibited IRF4, STAT6, and C/EBPb signaling and significantly increased inhibitory histone H3 lysine 27 tri-methylation (H3K27m3) on the promoters of M2-related genes in tumor-associated macrophages (Iwanowycz et al, 2016). In BALB/c nude mice xenograft with human hepatocellular cancer SMMC-7721 cells, emodin suppressed tumor growth and induced apoptosis with increases in ERK and p38 phosphorylation and suppression of p-JNK expression (Lin et al, 2016).…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice bearing EO771 or 4T1 breast tumors, emodin suppressed tumor growth by inhibiting macrophage infiltration and M2-like polarization, accompanied by increased T-cell activation and reduced tumor angiogenesis (Iwanowycz et al, 2016). At molecular level, emodin inhibited IRF4, STAT6, and C/EBPb signaling and significantly increased inhibitory histone H3 lysine 27 tri-methylation (H3K27m3) on the promoters of M2-related genes in tumor-associated macrophages (Iwanowycz et al, 2016). In BALB/c nude mice xenograft with human hepatocellular cancer SMMC-7721 cells, emodin suppressed tumor growth and induced apoptosis with increases in ERK and p38 phosphorylation and suppression of p-JNK expression (Lin et al, 2016).…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…The in vitro molecular mechanism showed that emodin activated ER stress and TRIB3/nuclear factor-kB signaling (Su et al, 2017). In mice bearing EO771 or 4T1 breast tumors, emodin suppressed tumor growth by inhibiting macrophage infiltration and M2-like polarization, accompanied by increased T-cell activation and reduced tumor angiogenesis (Iwanowycz et al, 2016). At molecular level, emodin inhibited IRF4, STAT6, and C/EBPb signaling and significantly increased inhibitory histone H3 lysine 27 tri-methylation (H3K27m3) on the promoters of M2-related genes in tumor-associated macrophages (Iwanowycz et al, 2016).…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…Emodin has immunomodulatory effects in cancer and immunity. It inhibits cell growth and metastasis through blocking the tumor-promoting feed forward loop between macrophages and breast cancer cells [394].…”
Section: Emodinmentioning
confidence: 99%
“…Emodin has long been used to treat chronic kidney diseases with few side effects (11). Recently, many studies have also documented laxative effects of emodin as well as its inhibitory effects on tumors (12), viruses (13), bacteria (14), and inflammation (15) without any major side effect. Furthermore, emodin is also available in China at a low cost.…”
mentioning
confidence: 99%